Intention to Use on the Use of E-Wallet Link Aja: How Important is Hedonic Motivation? - Jadmiko, Purbo; Pasha, Fikhrial; Najib Razali, Muhammad (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
The diversity of e-wallet products has changed many consumer shopping patterns. This study aims to analyze the factors that influence the intention to use. The approach used is to adopt the Technology Acceptance Model (TAM). The respondents of this study were the general public in the city of Padang (n = 100). Multiple regression analysis is used to test the research hypothesis with the help of the STATA application. The findings of this study indicate that the variables Perceived usefulness, perceived ease of use, and hedonic motivation have a positive and significant effect on the intention to use. Interesting findings in this study where the hedonic motivation variable has the largest proportion of the coefficient on intention to use the Link Aja e-wallet in Padang City. Apart from that, the reasons for using LinkAja are more dominated by the need to purchase/top up. The implications of this research can be adopted for e-wallet manufacturers to continue to increase the diversity of payment methods. Future research should consider cross-generational aspects, gender differences, and personality aspects so that research results can be better generalized.